Cost-effectiveness of mass drug administration for control of scabies in Ethiopia: a decision-analytic model - Hounsome, Natalia; Yirgu, Robel; Middleton, Jo; Cassell, Jackie A.; Fekadu, Abebaw; Davey, Gail (Frontiers in Health Services, 2024)
BackgroundThe strategies to control scabies in highly endemic populations include individual case/household management and mass drug administration (MDA). We used a decision-analytic model to compare ivermectin-based MDA and individual case/household management (referred to as “usual care”) for control of scabies in Ethiopia at different prevalence thresholds for commencing MDA.MethodsA decision-analytic model was based on a repeated population survey conducted in Northern Ethiopia in 2018–2020, which aimed to evaluate the secondary impact of single-dose ivermectin MDA for the control of onchocerciasis on scabies prevalence. The model estimates the number of scabies cases and costs of two treatment strategies (MDA and usual care) based on their effectiveness, population size, scabies prevalence, compliance with MDA, medication cost, and other parameters.ResultsIn the base-case analysis with a population of 100,000 and scabies prevalence of 15%, the MDA strategy was both more effective and less costly than usual care. The probability of MDA being cost-effective at the current cost-effectiveness threshold (equivalent to the cost of usual care) was 85%. One-way sensitivity analyses showed that the MDA strategy remained dominant (less costly and more effective) in 22 out of 26 scenarios. MDA was not cost-effective at scabies prevalence <10%, MDA effectiveness <85% and population size <5,000. An increase in the cost of ivermectin from 0 (donated) to 0.54 US$/dose resulted in a decrease in the probability of MDA being cost-effective from 85% to 17%. At 0.25 US$/dose, the MDA strategy was no longer cost-effective.ConclusionsThe model provides robust estimates of the costs and outcomes of MDA and usual care and can be used by decision-makers for planning and implementing scabies control programmes. Results of our analysis suggest that single-dose ivermectin MDA is cost-effective in scabies control and can be initiated at a scabies prevalence >10%.